Articulation of Traditional Medicines with Medical Officer - Cabieses, Fernando (1996)
It's been two decades since, at the Meeting of Alma Ata, members of the World Health Organization called attention to governments on the importance of Traditional Medicines in the plans, programs and strategies for Primary Care health. Some countries in Asia incorporating reaffirmed their Traditional Medical Systems in a wide range of levels in public health, as can be clearly seen in the activity of China and India.